Fenomena Kekerasan di Lingkungan Pendidikan - Ida Novianti (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Friend at school ideally have role as a partner, to motivate other student to do learning activity. Meanwhile, teacher role is as mentor, facilitator, supervisor, and role model for student. However, fact shows that bullying and violence case at school reaching frightened level. Bullying is a serious problem that can cause traumatic effect to the victim. Several factors causing bullying are family background, individual character, and school environment. Bullying can take a form like averse nickname, alienating, wrong issue, expelling, physical violence and aggression (pushing, beating, kicking), intimidation, theft, and with religion, ethnic, or gender based. Several strategies to stop bullying are adequate monitoring to student, and giving effective and distinct punishment to performer. Better communication between parent and teacher also important to resolute this problem. Theater have to give positive role model and give reinforcement,Â and school must proactive to formulate social skill learning program, problem solving, conflict management, and character education.Â